Fertility Behavior and Depression Among Women: Evidence From China - Yang, Hualei; Zheng, Xiaodong; Zhou, Ruyin; Shen, Zheng; Huang, Xinyu (Frontiers in Psychology, 2020)
Using data from the China Labor-force Dynamic Survey, this study employed logistic regressions to investigate the association between fertility behavior and depression among Chinese women. The empirical results show that in China, women having children were significantly less likely to have depressive symptoms (OR=0.651) compared to childless women. We also found a U-shaped relationship between fertility levels and depression in women. The results were robust to using the propensity score matching approach to address the sample selection problem. Further, our heterogeneity analysis demonstrated that the negative relationship between fertility level and depression was more significant among women who were in their 30s, lived in urban areas, and lived in high-income households. Compared to having male children (boys) (OR=0.874), having female children (girls) (OR=0.795) was more significantly associated with fewer depressive symptoms among women. In the meantime, we did not find a significant relationship between the childbearing period and depression. The paper discussed possible reasons for our findings and policy implications from the perspectives of the government, society, and family.